Effect of the Growth Stage of False Flax (Camelina sativa L.) on the Phenolic Compound Content and Antioxidant Potential of the Aerial Part of the Plant - Magdalena Karamać; Francesco Gai; Pier Giorgio Peiretti (Polish Journal of Food and Nutrition Sciences)
The phenolic compound profile and antioxidant potential of the false flax (Camelina sativa L.) plant, harvested at five morphological stages, that is, from the vegetative to the ripe seed-pod stage, have been investigated. False flax extracts were prepared using 80% (v/v) methanol, and the total phenolic content (TPC), the contents of the individual phenolics and antioxidant activity, measured as the Trolox equivalent antioxidant capacity (TEAC), ferric-reducing antioxidant power (FRAP), DPPH• scavenging activity and the ability to inhibit the oxidation of β-carotene-linoleic acid emulsion, were determined. The TPC of the plant, at different growth stages, ranged from 49.2 to 59.1 mg GAE/g of extract and from 1.46 to 3.10 mg GAE/g of fresh matter (FM). Four main phenolic compounds were identified (chlorogenic acid, rutin, quercetin 3-O-glucoside, and quercetin glycoside). The chlorogenic acid content and the sum of flavonoids increased in the extracts from the vegetative to the bud stage, reaching 35.9 and 49.5 mg/g of extract, respectively, and gradually decreased in the subsequent growth stages. The plant extracts at the bud and flowering stages generally had the highest antioxidant activity in the polar systems (TEAC, FRAP and DPPH assays). The ripe seed-pod stage showed the highest antioxidant potential in these conditions when the results were expressed on FM basis. The best antioxidant activity in the lipid emulsion system was shown for the false flax extracts at the flowering and ripe seed-pod stages. Our research has indicated the possibility of using the aerial part of C. sativa as a source of ingredients with protective antioxidant activity.